2019
DOI: 10.3390/ani9050248
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol in Sheltered Cows and Its Association with Other Welfare Indicators

Abstract: India, the country with the largest population of dairy cows in the world, has a policy of retiring abandoned and non-lactating cows in shelters, but the level of provision for their welfare in these shelters is unclear. Cows in 54 shelters across India were assessed for historic evidence of physiological stress, through determination of hair cortisol in 540 samples from 10 cows in each shelter by enzyme immunoassay. Animal-based and shelter resource-based welfare measures were recorded and correlations with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…It was found that hair cortisol was significantly higher in physiologically or clinically compromised cows, providing evidence for increased activation of the HPA axis upon (long lasting) stress in cows [ 28 ]. This was confirmed by Sharma et al [ 41 ], who performed a study with (old) cows in Indian shelters, where the environmental conditions are sometimes far from optimal, and concluded that hair cortisol level could be a useful biomarker of stress in cows when conducting studies under field conditions.…”
Section: Introductionmentioning
confidence: 64%
“…It was found that hair cortisol was significantly higher in physiologically or clinically compromised cows, providing evidence for increased activation of the HPA axis upon (long lasting) stress in cows [ 28 ]. This was confirmed by Sharma et al [ 41 ], who performed a study with (old) cows in Indian shelters, where the environmental conditions are sometimes far from optimal, and concluded that hair cortisol level could be a useful biomarker of stress in cows when conducting studies under field conditions.…”
Section: Introductionmentioning
confidence: 64%
“…Conversely, the hair cortisol concentration is a marker of cortisol secretion and stress over long periods of time [ 59 ]. Its quantification is increasingly used in psycho-neuro-endocrinological studies in humans, and, more recently, also in animal stress and welfare research, including sheep [ 31 , 58 , 59 , 60 , 61 ]. The sampling procedure, smooth and minimally invasive, and the extended time periods in which the data were obtainable from a sample refer make the hair cortisol titration an extremely useful biomarker for the assessment of chronical stress in animals, although, to date, no species-specific reference values are available.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding basic reproductive function is crucial for successful conservation breeding programs of endangered species, and it can be studied by monitoring circulating hormones [ 19 , 20 , 21 ]. Hormones can be measured in a variety of biological samples such as feces [ 22 , 23 , 24 ], urine [ 25 ], blood [ 26 ], saliva [ 27 ], milk [ 28 ], and hair [ 29 , 30 , 31 ]. Although circulating hormones in the blood give an accurate measurement, blood sampling for long-term monitoring of wild animals is challenging and stressful.…”
Section: Introductionmentioning
confidence: 99%